Flag - Crampton, W. G. (William G.) (Eyewitness books, 1989)
A photographic essay about flags from countries all over the world and such special flags as signal flags for ships and boats, flags for special festivals and sports, political flags and coats of arms. Also includes information about the meaning of shapes and colors on flags.